2022
DOI: 10.1111/luts.12432
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms in patients with small prostates: Smooth muscle proliferation and calcification might be causative factors

Abstract: Objectives: The current study is designed to evaluate and compare the histological changes in the surgical samples of prostate taken from patients undergoing transurethral resection of prostate (TURP) for benign prostate hyperplasia (BPH) with different sizes.Methods: Prostate surgical tissue samples were obtained from BPH patients undergoing TURP after taking informed consent. Ultrasound measure of prostatic weight and prostate-specific antigen (PSA) levels were obtained from the patients along with other cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous research has indicated that while it often arises as a consequence of scar tissue formation following prostatitis resolution, several factors, including chronic prostatitis, prostatic urine retention, prostatic duct stenosis, abnormalities in calcium and phosphorus metabolism, and psychosocial factors, may contribute to its development [12][13][14]. Epidemiological studies have also linked poor dietary habits (such as irregular breakfasts and consumption of fatty snacks), alcohol consumption, and certain work-related habits (like prolonged sitting, late-night work, and the habit of holding in urine) to an increased risk of calcification [15,16]. It was discovered that small calci-fication foci typically do not impact sperm quality; however, the formation of larger and coarser stones can have adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that while it often arises as a consequence of scar tissue formation following prostatitis resolution, several factors, including chronic prostatitis, prostatic urine retention, prostatic duct stenosis, abnormalities in calcium and phosphorus metabolism, and psychosocial factors, may contribute to its development [12][13][14]. Epidemiological studies have also linked poor dietary habits (such as irregular breakfasts and consumption of fatty snacks), alcohol consumption, and certain work-related habits (like prolonged sitting, late-night work, and the habit of holding in urine) to an increased risk of calcification [15,16]. It was discovered that small calci-fication foci typically do not impact sperm quality; however, the formation of larger and coarser stones can have adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) and frailty are common among older adults and remarkably affect their daily lives 1–9 . Both LUTS and frailty are related to multiple comorbidities and unfavorable outcomes, such as reduced physical activity, hospitalizations, falls, impaired cognition, and poor quality of life 10–19 . Furthermore, several studies have revealed close associations between LUTS and frailty 4–8 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Both LUTS and frailty are related to multiple comorbidities and unfavorable outcomes, such as reduced physical activity, hospitalizations, falls, impaired cognition, and poor quality of life. [10][11][12][13][14][15][16][17][18][19] Furthermore, several studies have revealed close associations between LUTS and frailty. [4][5][6][7][8] Since LUTS and frailty have complex relationships, it is difficult to define their association.…”
Section: Introductionmentioning
confidence: 99%